Fundamental Gross Motor Abilities In High-Risk Children At 5-6 Years – A Cross Sectional Study - SJ, Harshini; Muthusamy, Rajeswari; Ramachandran, Sivakumar; N Udayakumar, N Udayakumar; Pramila, C. Arockia (Journal of Neonatal Surgery, 2025)
Introduction: High risk new-borns are not only prone to develop apparent developmental disabilities but more subtle deficits might also occur which can be attributed to the outcome of a stormy neonatal period. Mastering of fundamental gross motor skills like jumping, hopping and catching beyond the rudimentary motor skills of sitting upright and walking becomes the precursors to more specialized movement and sport skills. The standard follow-up of many multicentred networks is around 2 years even though motor developmental delay is high and fundamental gross motor skills are ignored in high-risk children. This study intends to find the level of fundamental gross motor abilities and analyse the relationship between high-risk factors at the time of birth with gross motor development at 5-6 years. Materials and Methods: This cross-sectional study was carried out in Karthikeyan Child Developmental Unit in 30 high-risk children at 5-6 years of age. Birth records of the children were reviewed and the details of high-risk factors were recorded. Peabody Developmental Motor Scale-2 (PDMS 2) was used to evaluate gross motor development in high-risk children at 5-6 years. Results: Out of 30 high risk-children, 17 children were found to be preterm and 13 were low birth weight. The mean gross motor quotient of fundamental gross motor skills in high-risk children was found to be 81.5 which denotes a below average performance with deficits found in stationary and object manipulation component of PDMS 2. Spearman's correlation between the Gestational age/ Birth weight and gross motor quotient showed a significant positive correlation with a rs value of 0.73 and 0.76 respectively and p value of <0.01 conveying that higher gestation age and birth weight showed good gross motor development. Conclusion: Fundamental gross motor abilities of the high-risk children at 5-6 years shows below average performance and strong association between the gestational age/birth weight and gross motor abilities emphasizes the need for long term neuro-developmental follow up of these children and to address the subtle deficits earlier to attain their fundamental gross motor abilities appropriately.